Teaching Strategies and Students’ Performance in Mathematics in a Borderless Classroom - Roblon, Angelie; Cano Jr., Alfredo; Miñoza, Grechel; Recomo, Jenybabe; Monares, Jhetier; Arriola, Mark Angelo; Polancos, Queenie (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
As the educational sector shifted from traditional to borderless classrooms, having discussions through virtual platforms became the most popular option to keep the learning going amid the pandemic. This study investigated the teaching strategies of mathematics college instructors in college on the second-year mathematics students’ performance in borderless classrooms. It also determined how well the mathematics instructors adjusted to the situation, as evidenced by how and what teaching strategies they used in their classes. Fifteen mathematics instructors were recruited for the study using a random sampling technique. Findings revealed that some teachers were unfamiliar with various tools and platforms. Using the Pearson correlation coefficient, there is a significant positive relationship between the teaching strategies in the borderless classrooms and the student’s performance in mathematics r (13) = .49, p< .04. The Strategic Intervention Applied in Asynchronous Teaching (SIAAT) was proposed by which will ensure that students will continue to receive asynchronous learning in borderless classrooms.